FLUDARABINE-BASED LOW-INTENSITY CONDITIONING FOR FANCONI ANEMIA IS ASSOCIATED WITH GOOD OUTCOMES IN APLASTIC ANEMIA BUT NOT IN MDS - A SINGLE-CENTER EXPERIENCE - Biju George; Sohini Chattopadhyay; Sharon Lionel; Sushil Selvarajan; Anup Devasia; Anu Korula; Uday Kulkarni; Fouzia Aboobacker; Eunice Sindhuvi; Kavitha Lakshmi; Alok Srivastava; Aby Abraham; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Hematopoietic stem cell transplantation [HSCT] is the only curative option for Fanconi Anemia (FA) patients with hematological abnormalities.